Development of Student Worksheets based on the Discovery Learning Approach in the Automotive Light Vehicle Engineering Program at Vocational High Schools - Irfandi, Andi; Siraj; Nuraina (Indonesian Journal of Technical and Vocational Education Training, 2024)
This research aims to develop student worksheets based on the discovery learning approach. Designing Student Worksheets based on the discovery learning approach for class x automotive light vehicle engineering at state vocational high school 1 Seunuddon. Vocational Education Study Program in Mechanical Engineering fakultas keguruan dan ilmu pendidikan Malikussaleh University, 2024. This research aims to describe the design, feasibility and learning outcomes of class automotive. This research uses a mix methods approach. This research used a sample consisting of 8 class X students majoring in automotive engineering. Data collection uses questionnaires, documentation, interviews and observations, data analysis techniques use percentage qualitative analysis through data collection and drawing conclusions. The research results show student learning outcomes. The media I results gave an overall score with a percentage of 89.28% and media experts II gave an overall score with a percentage of 89.28%. The average percentage of the two validators shows the "very feasible" category. Thus, this student worksheet is very suitable for usefor learning by teachers and students. Where the value obtained has passed the learning objective achievement criteria value which has been determined as a reference for the success of the learning process at 75 with a percentage of 78.75%, thus it can be concluded that the value obtained by the students is categorized as complete. Thus, this student worksheet is suitable for use by teachers and students for a more effective learning process.